2022
DOI: 10.3855/jidc.14924
|View full text |Cite
|
Sign up to set email alerts
|

Reducing length of hospital stay with colchicine

Abstract: Introduction: Colchicine is an ancient agent with well-known anti-inflammatory effects and commonly used in treatment of hyperinflammatory conditions. It has been argued that colchicine could be an appropriate treatment option in COVID-19 to control hyperinflammatory response. Here in this study, we aimed to investigate the impact of colchicine on outcomes of COVID-19 in our inpatient cohort. Methodology: In this retrospective cohort study, hospitalized COVID-19 patients were investigated. Demographics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In considering potential mitigating treatments, glucocorticoids 43–46 may contribute to the reduction of autoantibodies, and in turn decrease NETosis and enhance recovery from NETosis‐related conditions. Colchicine and DNase I are both recognized as therapies that target NETs, 47–51 but more research is warranted to ascertain their effectiveness in managing post‐COVID‐19 vaccination side effects. These findings offer crucial insights for refining risk assessments and development of future vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…In considering potential mitigating treatments, glucocorticoids 43–46 may contribute to the reduction of autoantibodies, and in turn decrease NETosis and enhance recovery from NETosis‐related conditions. Colchicine and DNase I are both recognized as therapies that target NETs, 47–51 but more research is warranted to ascertain their effectiveness in managing post‐COVID‐19 vaccination side effects. These findings offer crucial insights for refining risk assessments and development of future vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Karakaş et al noted, even when comparing low doses of colchicine of 1 with 0.5 mg per day, beneficial effect of higher colchicine dosages. 33 …”
Section: Discussionmentioning
confidence: 99%
“…32 Karakaş et al noted, even when comparing low doses of colchicine of 1 with 0.5 mg per day, beneficial effect of higher colchicine dosages. 33 T A B L E 7 Pooled data, separated by initial loading dose. Increasing doses of colchicine positively enhances the treatment of COVID-19, but the doses administered so far are far from effective.…”
Section: Two Different Strategies For Treating Covid-19mentioning
confidence: 99%
“…Retrospective studies of colchicine in patients with COVID-19 have already shown good results, with no major adverse effects in non-hospitalized [ 33 ] and hospitalized patients in terms of reduction in hospitalization and recovery time [ 34 36 ], progression to intubation [ 37 ], and mortality [ 34 , 35 , 37 39 ].…”
Section: Discussionmentioning
confidence: 99%